ANALISIS PENGGUNAAN BEASISWA BIDIKMISI DAN PENGARUHNYA TERHADAP HASIL BELAJAR MAHASISWA JURUSAN PIPS FKIP UNIVERSITAS RIAU - Mahariati, Mahariati; Sumarno, Sumarno; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstack: This research was conducted with the aim to find out the analysis of the use of bidikmisi scholarships and its effect on student learning outcomes majoring in PIPS FKIP Riau University. The populations on this research were 40 students and the samples to be studied were 40 people. Data analysis used questionnaires and documentation. Data analysis used linear regression analysis. The results of the study show that the largest use of scholarships is in the indicator of food and beverage costs and The smallest use of scholarship is in the indicator of transportation costs. Overall the use of bidikmisi scholarships had a significant effect on learning outcomes. But seen the indicator (type of use) there was indicators that have no significant effect it was the cost indicator of clothing and the indicator of transportation costs. While indicators that have a significant effect are food and beverage coats, housing costs, and equipment costsKey Words: Bidikmisi Scholarship, the learning result